The Effect Of Empowering Leadership and Organizational Culture On The Employee Performance Zt Pt. Bank Sumut kcp Sidamanik - Tarigan, Widya Nadasari Br; Harahap, Kartini (Cattleya Darmaya Fortuna, 2023)
This study seeks to analyze the influence of empowering leadership and organizational culture on employee performance at PT. Bank SUMUT Sub-Branch Office Sidamanik. The form of research used in this study is quantitative research with an associative approach. Sampling was carried out through a saturated sampling technique involving 35 working people. Data collection techniques are obtained through primary data obtained through the distribution of direct questionnaires and secondary data obtained through books, journals, which are related to this study. The results of the study showed that the variables empowering leadership (X1) and organizational culture (X2) together had a significant effect on employee performance (Y). The coefficient of determination test shows that there is a fairly close relationship between empowering leadership and organizational culture to employee performance with an R value of 0.692. Through the adjusted R square value, it is also known that the variables of empowering leadership and organizational culture contributed 44.7% to the remaining employee performance variables by 55.3% influenced by other variables that were not described in this study.